-2(3x - 15) = 60. solve for x

2 answers

To solve the equation \(-2(3x - 15) = 60\), follow these steps:

  1. Distribute \(-2\) to both terms inside the parentheses:

    \[ -2 \cdot 3x + (-2) \cdot (-15) = 60 \]

    This simplifies to:

    \[ -6x + 30 = 60 \]

  2. Next, isolate the term with \(x\). Subtract \(30\) from both sides:

    \[ -6x + 30 - 30 = 60 - 30 \]

    This simplifies to:

    \[ -6x = 30 \]

  3. Now, solve for \(x\) by dividing both sides by \(-6\):

    \[ x = \frac{30}{-6} \]

    This simplifies to:

    \[ x = -5 \]

So, the solution is:

\[ \boxed{-5} \]

can I ask another question?